Risk factors of short-term stroke recurrence in patients with minor ischemic cerebrovascular events - Ghandehari, Kavian (Isfahan Cardiovascular Research Center, Isfahan University of Medical Sciences, 2013)
BACKGROUND: Assessing the risk of recurrent ischemic events in patients with transient ischemic attack (TIA) and minor ischemic stroke (MIS) is of a great importance in clinical practice. METHODS: Consecutive patients with TIA or MIS who were visited in Ghaem Hospital, (Mashhad, Iran) were enrolled in a prospective cohort study during 2010 to 2011. Diagnosis of TIA or MIS was accomplished by a stroke neurologist. Only those who presented within 24 hours from the onset of symptoms were recruited. MIS was considered as an ischemic stroke with National Institutes of Health Stroke Scale (NIHSS) < 4. The endpoint of the study was a new ischemic cerebrovascular event or vascular death in 90 days and additionally in 3 days. The decision to admit and type of treatment in each case was left to the discretion of the stroke neurologist. The association between 20 potential factors with recurrent ischemic events in 3 and 90 days was investigated using univariate and multivariate analysis (MVA). RESULTS: 393 TIA patients (238 males and 155 females) and 118 MIS patients (77 males and 41 females) were enrolled in the study. Stroke occurred in 117 (23.2%) patients, TIA in 99 (19.6%), and there was 11 (2.2%) vascular deaths within 3 months in the total 511 patients with minor ischemic events. Crescendo TIAs and multiple TIAs were associated with greater risk of stroke in 3 days in a univariate analysis (OR = 5.12, P < 0.001) and (OR = 3.98, P = 0.003), respectively. Patients with index stroke had 11.5% lower risk of recurrent stroke in 3 days than patients with index TIA in multivariate analysis (OR = 0.115, P = 0.039). Diabetes was independently associated with 3 months stroke recurrence in the patients with minor ischemic events (OR = 2.65, P = 0.039). CONCLUSION: Multiple and crescendo TIAs are the main predictors of stroke recurrence, derived from the univariate analysis of the patients with minor ischemic events.